2019
DOI: 10.1021/acssynbio.8b00453
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Evaluation of Site-Specific Recombinant Gene Expression for Programmable Mammalian Cell Engineering

Abstract: Many branches of biology depend on stable and predictable recombinant gene expression, which has been achieved in recent years through targeted integration of the recombinant gene into defined integration sites. However, transcriptional levels of recombinant genes in characterized integration sites are controlled by multiple components of the integrated expression cassette. Lack of readily available tools has inhibited meaningful experimental investigation of the interplay between the integration site and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(70 citation statements)
references
References 70 publications
1
67
0
Order By: Relevance
“…For this purpose, well-characterized and transcriptionally active regions are identified that enable high stability and continuous expression of the transgenes over long periods of time [206]. Such sites can be identified either computationally, based on transcriptome data, by random selection [207][208][209] or using recombinase pseudosites [210] or viral vectors [208]. For reuse, "landing-pads" containing recombination sites and selection markers [208,210] are inserted into these stable sites, allowing easy integration of heterologous DNA of interest and thereby facilitating the development of stable producer cell lines with a known genomic environment [208].…”
Section: Maintaining Stabilitymentioning
confidence: 99%
“…For this purpose, well-characterized and transcriptionally active regions are identified that enable high stability and continuous expression of the transgenes over long periods of time [206]. Such sites can be identified either computationally, based on transcriptome data, by random selection [207][208][209] or using recombinase pseudosites [210] or viral vectors [208]. For reuse, "landing-pads" containing recombination sites and selection markers [208,210] are inserted into these stable sites, allowing easy integration of heterologous DNA of interest and thereby facilitating the development of stable producer cell lines with a known genomic environment [208].…”
Section: Maintaining Stabilitymentioning
confidence: 99%
“…Steady improvements in cell line development, media formulation, and bioprocessing now enable production yields exceeding 10 g/L from a fed-batch culture. Emerging resources, including the CHO and hamster genome sequence [3][4][5][6][7][8] and genome editing tools [9][10][11][12][13][14] now allow researchers to rely less on largely empirical, "trial-and-error" approaches to CHO cell line development, and move towards a more rational engineering approach, in pursuit of novel CHO lines with tailored, superior attributes [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Steady improvements in cell line development, media formulation, and bioprocessing now enable production yields exceeding 10 g/L from a fed-batch culture. Emerging resources, including the CHO and hamster genome sequence [3][4][5][6][7][8] and genome editing tools [9][10][11][12][13][14] now allow researchers to rely less on largely empirical, "trial-and-error" approaches to CHO cell line development, and move towards a more rational engineering approach, in pursuit of novel CHO lines with tailored, superior attributes [15][16][17][18]. However, cell line instability, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed quantification of chromosomal instabilities in production cell lines has indicated that certain chromosome sites are less prone to instability than others [42]. This observation has suggested that transgene loss may be avoided by targeting transgenes to these stable chromosomal areas, an option now possible through the development of targeted transgene integration techniques [12,[43][44][45]. Further studies used gene knock-outs (ATR and BRCA1, respectively) to increase product titer by increasing transgene copy number amplification [46,47], but whether these knock-outs are able to sustain high production in long-term culture has remained unclear.…”
Section: Introductionmentioning
confidence: 99%